THE INFLUENCE OF PARENTING PATTERNS ON TANTRUM INCIDENTS IN TODDLERS IN THE WORKING AREA OF THE LABUHAN RUKU COMMUNITY HEALTH CENTER, TALAWI DISTRICT, BATUBARA REGENCY IN 2022 - Faziah, Putri; Sinaga, Siti Nurmawan; Hawani; Juliana Munthe; Vivi Restiyani; Indriani, Noni; Ananda, Rosdiani (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: This study investigates the influence of parenting styles on tantrum incidence among toddlers in the work area of Labuhan Ruku Public Health Center. Using a descriptive-analytic method with a cross-sectional design, the study involved 40 respondents. The results indicate that neglectful parenting was the most prevalent style, while distress tantrums were the most common type. A significant association (p = 0.005) was found between parenting styles and tantrum types. These findings highlight the need for parenting interventions to reduce tantrum behavior in toddlers.